Amorphous solid dispersions of carvedilol along with pH‐modifiers improved pharmacokinetic properties under hypochlorhydoria. (25th April 2018) - Halder, Shimul; Tabata, Aiko; Seto, Yoshiki; Sato, Hideyuki; Onoue, Satomi
Abstract: Carvedilol (CAR) belongs to biopharmaceutics classification system class‐II drugs, with poor aqueous solubility and pH‐dependent solubility. The present study aimed to develop a novel amorphous solid dispersion (ASD) of CAR with acidic counter ions for pH modifications in microenvironment to improve the pharmacokinetic properties under hypochlorhydric conditions. CAR‐ASD was prepared by freeze‐drying in combination with counter ions and hydroxypropyl cellulose, and their physicochemical properties including dissolution behavior, storage stability, and photostability were characterized. Pharmacokinetic studies were carried out after oral administration of CAR samples in both normal and omeprazole‐treated (30 mg/kg, p.o .) rats as a hypochlorhydria model. Among the tested six counter ions, citric acid (CA) was found to be a preferable pH‐modifier of CAR with respect to the dissolution profile and photostability (both potency and colorimetric evaluation). In CAR‐ASD formulation with 50% loading of CA (CAR‐ASD/CA50), amorphization of CAR was observed during the preparation process. After the oral administration of crystalline CAR in rats under hypochlorhydric condition, there was a 34.4% reduction in the systemic exposure of CAR compared with that in normal rats. However, orally‐dosed CAR‐ASD/CA50 resulted in limited alterations of pharmacokinetic behavior between normal and omeprazole‐treated rats. From these findings, addition of CA as pH‐modifier in CAR‐ASD might provide consistent pharmacokinetic behavior of CAR even under hypochlorhydric conditions.